2014
DOI: 10.1016/j.scriptamat.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature creep resistance of Co-based metallic glasses

Abstract: The room-temperature creep resistance of the Co 56 Ta 9 B 35 metallic glass was determined by a nanoindentation technique. Results showed that the creep curves were described by a generalized Kelvin model. The low creep strain-rate sensitivity parameter and creep rate derived from the displacement-holding time curves demonstrated the high creep resistance of the Co 56 Ta 9 B 35 metallic glass. The deformation mechanism causing the nanoindentation creep was discussed based on the "shear transformation zone" con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Additionally, as Li et al [4] and Yu et al [13] proposed, the indentation creep obeys an empirical power law of the form:…”
Section: Calculationsmentioning
confidence: 99%
“…Additionally, as Li et al [4] and Yu et al [13] proposed, the indentation creep obeys an empirical power law of the form:…”
Section: Calculationsmentioning
confidence: 99%
“…While atomistic simulations have suggested that such loads can produce irreversible changes in the glass structure [216], creep-like behavior at RT was experimentally observed through uniaxial elastostatic compression tests in mm-sized MG samples [217,218]. Hence, time-dependent plastic deformation, or creep, at RT in a wide variety of MGs has been investigated using nanoindentation [219][220][221][222][223][224][225][226][227]. Results show that creep occurs at RT irrespective of whether T g is low or high, and the measured response is sensitive to both intrinsic material features such as the chemical composition [228] and the nature of initial structural defects [223,225], as well as external testing conditions such as the [223,226] and imposed strain [224,227]).…”
Section: Time-dependent Deformationmentioning
confidence: 99%
“…Creep behavior is a critical issue of practical engineering significance for the applications of BMGs. Recently, the creep behaviors of BMGs have been reported using compression tests and nanoindentation technology [6][7][8][9][10][11][12][13][14][15]. Huang et al studied the room temperature creep behaviors of a Fe 41 Co 7 Cr 15 Mo 14 C 15 B 6 Y 2 BMG using the nanoindentation technique and found that the creep exponent varied with the peak load or loading rate, which has been interpreted based on the shear transformation zone theory [6].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al studied the room temperature creep behaviors of a Fe 41 Co 7 Cr 15 Mo 14 C 15 B 6 Y 2 BMG using the nanoindentation technique and found that the creep exponent varied with the peak load or loading rate, which has been interpreted based on the shear transformation zone theory [6]. Yu et al suggested that the nanoindentation creep behaviors of Co 56 Ta 9 B 35 metallic glass could be described by a Kelvin model [7]. However, it should be noted that the nanoindentation creep is sensitive to the ambient environment, and the different holding times used in creep tests in previous literature have caused paradoxical results.…”
Section: Introductionmentioning
confidence: 99%